Unattended Radar Station Design for Dewline Application. - Abriel,W E; Bell,S E; Golden,J R; Gorham,J T; Johnson,R M (1978)
This report examines the feasibility of implementing and maintaining a string of Unattended Radar Stations in the Arctic. The study is conceptual relative to design, installation, operation, maintenance, and support of Unattended Stations and attendant problems such as security, reliability, maintainability, availability, and life cycle cost. Cost Drivers are identified and potential solution alternatives with recommendations presented. The conclusion is that, with reasonable development, economical Unattended Arctic Radar Stations are possible. (Author) See also Volume 1, AD-A059 721.